Design of a 2.5kW DC/DC fullbridge converter - Andersson, Christian (My University, 2011)
In this thesis, an isolated 2.5kW fullbridge DC/DC converter has been designed and analyzed regarding its efficiency and weight. By increasing the switching frequency, the magnetic components in the converter can be made smaller, in this thesis a switching frequency of 20 kHz has been compared with a switching frequency of 100 kHz. The transformer in the converter can be winded in different ways which will affect the rectification on the low voltage side, this thesis has analyzed the center-tap- and fullwave-bridge -rectification. Efficiency improvement-techniques such as zero voltage switching, ZVS, and synchronous rectification have also been analyzed. It was found that by going from 20 kHz to 100 kHz the converter weight can be reduced by approximate 10% and by using the center-tap- instead of fullwave-bridge –rectification the efficiency can improve by approximately 1-3%, from around 94% up to approximately 97% efficiency.
Keywords: Elkraftteknik; Electric power engineering